Abafi Aigner Lajos and the secret societies in Banat in the second half of the 18th century - Varga, Attila (Swedish Journal of Romanian Studies, 2026)
This study analyses the contributions of Abafi Aigner Lajos, one of the most significant figures in Central European Masonic historiography, to our understanding of Masonic lodges and secret societies in the Banat region during the second half of the 18th century. Although Abafi is internationally recognised, he remains relatively unknown in Romanian historiography, primarily due to the inaccessibility of his seminal works, which are written in Hungarian and German. This article emphasises the pivotal role he played in exploiting the Old Archives of Hungarian Freemasonry, which were subsequently destroyed, and the significance of his methodology, which was grounded in primary sources. Drawing on Abafi’s research, the paper distinguishes clearly between Masonic lodges and secret societies, demonstrating that the latter often pursued radical political objectives that were distinct from the philanthropic and cultural ideals of Freemasonry. A case study of Timișoara reveals the coexistence and rivalry between the Masonic lodge Zu den 3 weissen Lilien [At the three white lilies] and societies such as the Rosicrucians, the Illuminati and the Order of the Rose in a context marked by the Enlightenment, urbanisation and profound social transformation. The research emphasises the significance of Freemasonry and secret societies as catalysts for modernity and societal change in the Banat region during the Enlightenment era.